Efficient Multicomponent Synthesis of Spirooxindole Derivatives Catalyzed by Copper Triflate. (31st December 2021) - Wu, Chunlei; Liu, Jian; Kui, Du; Lemao, Yu; Yingjie, Xu; Luo, Xiang; Meiyang, Xi; Shen, Runpu
Abstract: A simple and efficient method for the synthesis of spirooxindole derivatives via a three-component reaction of isatin, 5-aminopyrazole, and 1, 3-dicarbonylcompounds (or β-​oxo-benzenepropanenitril​e) catalyzed by copper triflate in ethanol is described. The advantages of this method include high efficiency, mild reaction conditions, recoverable catalyst, and environmentally benign conditions.